Characterization of mechanical and fracture behaviour in nano-silicon carbide-reinforced vinyl-ester nanocomposites - Alhuthali, Abdullah; Low, It Meng (Taylor & Francis Inc., 2013)
Vinyl-ester/nano-silicon carbide nanocomposites were synthesised and investigated in terms of their mechanical and fracture properties. Results show that the addition of nano-SiC particles increases modulus and strength, but reduces toughness. The enhancement in strength for nanocomposites was attributed to good interfacial adhesion and good degree of dispersion. The experimental data for elastic modulus were modelled using several theoretical models. The excellent agreement with the experimental data for elastic modulus given by the Guth and Kerner models indicate that the degree of dispersion and the quality of particle/matrix adhesion were both important considerations for the prediction of elastic modulus.